Analysis of the perception of health professionals regarding the incorporation of emerging technologies in their practice - Infantes, Manuel Silva (2023)
Introduction: healthcare is currently in the midst of a technology-driven revolution. Emerging technologies (ETs) are disrupting the practice of healthcare professionals in ways that once seemed futuristic, but are now an everyday reality in clinics and hospitals around the world. Objective: to analyze the perception of health professionals regarding the incorporation of emerging technologies in their practice. Methods: it is a quantitative, descriptive, non-experimental, cross-sectional study, whose sample was 107 health professionals who work in different health centers in Lima. The survey technique was used and the instrument was the questionnaire. Results: the participants perceived the incorporation and use of TE in their practice by 63,55 % (68) at a moderate level, 20,56 % (22) reported a high level, while 15,89 % indicated a low level. Conclusions: it was possible to specify a moderate level in the incorporation and use of TE, suggesting an intermediate position in technological adoption in medical care. This provides a solid foundation for future advances and improvements in the implementation of TE in medical practice.